Got plenty of nothing: cosmic voids as a probe of particle dark matter. Issue 11 (1st November 2022) - Arcari, S.; Pinetti, E.; Fornengo, N.
Abstract: The search for a particle dark matter signal in terms of radiation produced by dark matter annihilation or decay has to cope with the extreme faintness of the predicted signal and the presence of masking astrophysical backgrounds. It has been shown that using the correlated information between the dark matter distribution in the Universe with the fluctuations of the cosmic radiation fields has the potential to allow setting apart a pure dark matter signal from astrophysical emissions, since spatial fluctuations in the radiation field due to astrophysical sources and dark matter emission have different features. The cross-correlation technique has been proposed and adopted for dark matter studies by looking at dark matter halos (overdensities). In this paper we extend the technique by focusing on the information on dark matter distribution offered by cosmic voids, and by looking specifically at the gamma-ray dark matter emission: we show that, while being underdense and therefore producing a reduced emission as compared to halos, nevertheless in voids the relative size of the cross-correlation signal due to decaying dark matter vs. astrophysical sources is significantly more favourable, producing signal-to-background ratios S/B (even significantly) larger than 1 for decay lifetimes up to 2 × 10 30 s. This is at variance with the case of halos, where S/B is typically (even much) smaller than 1. We show that forthcoming galaxy surveys such as Euclid combined with future generation gamma-ray detectors with improved specifications have the ability to provide a hint of such a signal with a predicted significance up to 5.7 σ for galaxies and 1.6 σ for the cosmic shear. The bound on the dark matter lifetime attainable exploiting voids is predicted to improve on current bounds in a mass range for the WIMP of 25 ÷ 900 GeV.